2013
DOI: 10.1007/s11010-013-1821-5
|View full text |Cite
|
Sign up to set email alerts
|

The AKT/mTOR pathway mediates neuronal protective effects of erythropoietin in sepsis

Abstract: Sepsis is one of the most common causes of mortality in intensive care units. Although sepsis-associated encephalopathy (SAE) is reported to be a leading manifestation of sepsis, its pathogenesis remains to be elucidated. In this study, we investigated whether exogenous recombinant human erythropoietin (rhEPO) could protect brain from neuronal apoptosis in the model of SAE. We showed that application of rhEPO enhanced Bcl-2, decreased Bad in lipopolysaccharide treated neuronal cultures, and improved neuronal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…In the present study, the increased activation of the AKT pathway was accompanied by decreased inflammatory cytokines, further supporting the idea that AKT participates in the activation of M2 macrophages 34. Additionally, the present study is consistent with recent studies showing that AKT plays a protective role in sepsis [35][36][37]. SIRT1 shows strong anti-inflammation activity [38].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the increased activation of the AKT pathway was accompanied by decreased inflammatory cytokines, further supporting the idea that AKT participates in the activation of M2 macrophages 34. Additionally, the present study is consistent with recent studies showing that AKT plays a protective role in sepsis [35][36][37]. SIRT1 shows strong anti-inflammation activity [38].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to its known function in erythropoiesis, EPO has been reported to exert antiapoptotic, antiinflammatory, antioxidative, and neurotrophic properties [6]. EPO is an important mediator of the adaptive response to metabolic stress, which is an endogenous mediator of neuroprotection in various central nervous system disorders [7][8][9]. Accumulating evidence has demonstrated that exogenous EPO is beneficial during systemic sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…The growth factor and cytokine erythropoietin (EPO) activates Akt through its phosphorylation of serine 473 [70, 71] and prevents vascular cell demise through silent mating type information regulator 2 homolog 1 (SIRT1) cell longevity pathways [72]. EPO utilizes Akt to block cell injury during Aβ exposure [26], promote the survival of retinal ganglion cells during N-methyl-d-aspartate (NMDA) toxicity [73], enhance the myocardial protective function of mobilized peripheral blood mononuclear cells [74], foster anti-inflammatory effects [75], protect against sepsis [76], limit renal cell injury [77], and limit cellular injury during models of oxidative stress [7881]. Similar to EPO, other trophic factors also rely upon the PI 3-K and Akt pathways to foster cellular survival during toxic environments such as insulin-like growth factor-1 (IGF-1) [56], insulin [82], and brain derived neurotrophic factor [83].…”
Section: Wisp1 Signalingmentioning
confidence: 99%
“…mTORC2 also includes mLST8 and Deptor, but has additional components that are Rictor (Rapamycin-Insensitive Companion of mTOR), the mammalian stress-activated protein kinase interacting protein (mSIN1), and the protein observed with Rictor-1 (Protor-1) [136, 137]. Similar to WISP1, mTOR signaling is associated with PI 3-K, Akt, forkhead transcription factors, PRAS40, AMP activated protein kinase (AMPK), and p70 ribosomal S6 kinase (p70S6K) to affect cellular survival through programmed cell death pathways that involve apoptosis, autophagy, and necroptosis [60, 62, 63, 76, 79, 139149]. For example, Akt can control mTORC1 activity through the modulation of hamartin (tuberous sclerosis 1)/tuberin (tuberous sclerosis 2) (TSC1/TSC2) complex, an inhibitor of mTORC1 [150152].…”
Section: Wisp1 Signalingmentioning
confidence: 99%